DIFICULDADES PARA A REALIZAÇÃO DE AVALIAÇÕES DO CICLO DE VIDA DA INDÚSTRIA CIMENTEIRA NACIONAL - Silva, Ana Isabela Soares Martins da; Teles, Camila Correia; Silva Jr, Felix Alves da (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper presents the difficulties in the use of the Life Cycle Assessment in the national cement industry. To do so, the context of the implementation of the Life Cycle Assessment tool, its emergence, and expansion, as well as the good sustainability practices of the Brazilian cement industry are addressed. However, although there are sustainable practices exemplary of this industrial follow-up, the difficulties still prevail for the realization of this environmental tool in the Brazilian industrial park, being pointed out these impediments.